LABA AKUNTANSI DAN NET PROFIT MARGIN TERHADAP RETURN SAHAM PERUSAHAAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Ivana Brilliani Subagio; Irwan Irwan; Thobias E.D. Tomasowa (P3M- Politeknik Negeri Kupang, 2021)
The capital market is a means of funding for companies and other institutions (eg the government), and for investing activities. Thus, the capital market various facilities and infrastructure for buying and selling activities and other related activities. Where there is a sale and purchase of securities by investors against issuers. In selecting a company to be invested in by investors, several things such as stock returns and accounting profits are one of the triggers for investors to invest. Therefore, the authors are interested in raising this topic into a study with the following objectives; To find out the effect of Accounting Profit, Net Profit Margin on the Stock Returns of companies on the IDX. To determine the simultaneous effect of Accounting Profit and Net Profit Margin on the Stock Return of companies listed on the IDX. This study uses empirical research methods. The type of data source used is the financial statements of companies listed on the IDX. The research was conducted using 46 property and real estate companies listed in Indonesia Stock Exchange by selecting sample taken (purposive sampling) because there are certain consideration over a periode of 4 year (2018-2021). This research uses multiple regretion with SPSS. These result indicate that there is simultaneous and partially significant effect among Accounting Income and Net Profit Margin to Stock Return